2017
DOI: 10.1002/brb3.631
|View full text |Cite
|
Sign up to set email alerts
|

Learning and memory disabilities in IUGR babies: Functional and molecular analysis in a rat model

Abstract: IntroductionIntrauterine growth restriction (IUGR) is the failure of the fetus to achieve its inherent growth potential, and it has frequently been associated with neurodevelopmental problems in childhood. Neurological disorders are mostly associated with IUGR babies with an abnormally high cephalization index (CI) and a brain sparing effect. However, a similar correlation has never been demonstrated in an animal model. The aim of this study was to determine the correlations between CI, functional deficits in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…have recently shown WM microstructural alterations in children with ADHD using imaging data 21 . The dorsal hippocampus is associated with the cognitive functions that are impaired in ADHD children 22 . Rodent models of FGR exposed to hypoxia have shown that astrocyte accumulation and impaired myelination accompanies the WM injury after birth 23 .…”
Section: Discussionmentioning
confidence: 99%
“…have recently shown WM microstructural alterations in children with ADHD using imaging data 21 . The dorsal hippocampus is associated with the cognitive functions that are impaired in ADHD children 22 . Rodent models of FGR exposed to hypoxia have shown that astrocyte accumulation and impaired myelination accompanies the WM injury after birth 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus, a medial cortical structure required for forming new memories and learned behaviors ( Eichenbaum, 2000 ), is divided into the dentate gyrus (DG) and cornu ammonis (CA) fields in both humans and rodents, and is particularly susceptible to IUGR injury ( Gilchrist et al, 2018 ). Both children and animal models with IUGR have shown reductions in hippocampal volume by magnetic resonance imaging and correlated poorer memory performance ( Isaacs et al, 2000 ; Mallard et al, 2000 ; Lodygensky et al, 2008 ; Camprubí Camprubí et al, 2017 ). Multiple experimental models of IUGR have also indicated that both the neuron number and dendritic–axonal morphologies within the DG, CA1, and CA3 are altered following uteroplacental insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired cognitive development associated with LBW has also been studied in a variety of animal models, most frequently in rats and sheep [although contrary to pigs and humans, LBW has to be experimentally induced in these models—( 8 )]. For example, LBW has been linked to spatial memory deficits in rats ( 9 ). Together, these findings suggest that LBW could have a long-term impact on cognitive functioning.…”
Section: Introductionmentioning
confidence: 99%